EVALUASI IMPLEMENTASI KEBIJAKAN GURU PENDIDIKAN AGAMA (GPA) PADA SEKOLAH UMUM DI PROVINSI BALI - Abdul Kadir Ahmad; Lisa'diyah Ma'rifataini (Badan Litbang dan Diklat Kementerian Agama RI, 2021)
AbstractCrucial issues with religius education teachers (GPA) policies are related to coaching, career development, welfare and recruitment. This research approach is qualitative with descriptive type. Data collection uses in-depth interviews, participatory observations, and document studies. The purpose of this study was to determine the implementation of GPA policies on the four problems above, problems and solutions. The informants of this study were the Kasi at the Education Office, the Head of the Provincial Government, the Head of the Division and the Kasi at the Ministry of Religion, PA Supervisors and PA Teachers. The results showed that the GPA guidance policy was not optimal due to funding constraints, the limited number of supervisors covering very large coverage areas. Regarding career development, GPAs experience difficulties in writing scientific papers and require seminars or competency tests when they are promoted from IV / A to IV / B. Regarding welfare, non-PNS GPAs are constrained from participating in certification and inpassing because they have to include a decree from the Mayor / Regent and GPA who have not been certified due to limited quota There are three types of religious teachers in schools, namely those appointed by the Ministry of Religion, the Regional Government, and the Education Office, where the GPA data is always different and there is no coordination. In order to meet the lack of GPA in schools, the Ministry of Religion needs to appoint GTT religious teachers or contract teachers who are funded by the APBN, just as the Regional Government appoints GTT religious teachers who are funded by the APBD.AbstrakMasalah krusial kebijakan Guru Pendidikan Agama (GPA) adalah terkait pembinaan, pengembangan karier, kesejahteraan dan rekrutmen. Pendekatan penelitian ini kualitatif dengan tipe Deskriptif. Pengumpulan data menggunakan in-depth interview, participatory observation, dan document studies. Tujuan penelitian ini adalah untuk mengetahui implementasi kebijakan GPA terhadap empat masalah di atas, problematika dan solusi. Informan penelitian ini adalah Kasi pada Dinas Pendidikan, Kabid di Pemda Provinsi, Kepala Bidang dan Kasi di Kemenag, Pengawas PA dan Guru PA. Hasil penelitian menunjukkan bahwa kebijakan pembinaan GPA belum optimal karena terkendala pendanaan, keterbatasan jumlah pengawas yang Coverage areas sangat luas. Terhadap pengembangan karier, GPA mengalami kesulitan dalam penulisan karya tulis ilmiah dan keharusan seminar atau uji kompetensi ketika kenaikan pangkat dari IV/A ke IV/B.Â Terkait kesejahteraan, GPA non PNS terkendala untuk mengikuti sertifikasi dan inpassing karena harus menyertakan SK dari Walikota/Bupati dan GPA yang belum sertifikasi karena kuota terbatas. TerdapatÂ tiga jenis guru agama di sekolah yakni diangkat oleh Kemenag, Pemda, dan Dinas Pendidikan, di mana data GPA selalu berbeda dan belum ada koordinasi. Guna terpenuhi kurangnya GPA di Sekolah, Kemenag perlu mengangkat guru agama GTT atau guru kontrak yang dibiayai oleh APBN, seperti halnya Pemda mengangkat guru agama GTT yang dibiayai APBD.